The Mad Doctors: Medicine and Literature in Finisecular Spain - Cardwell, Richard A. (1996)
This essay forms the prolegomenon to what will be a major study of a particular aspect of the history of ideas and the cultural experience in Spain between 1880 and 1920 presently being written. This book will consider and analyse the relationships, interfaces and interpenetrations of artistic endeavour - painting, the decorative arts, literature and criticism - and culture, in the broadest sense, with the sciences, especially the medical sciences. The study will be principally concerned with literature and the critical essay but, necessarily, will trace the process of exchange which had begun earlier in the century and will project its impact on the cultural experience of the 1920s. In so doing, the study will challenge many of the hallowed tenets of literary history, not the least the theory which posits two antagonistic finisecular literary groups, modernismo and Generation of 1898.